What we can learn about Mars from the magnetism of returned samples - Benjamin P. Weiss; Elias N. Mansbach; Clara Maurel; Courtney J. Sprain; Nicholas L. Swanson-Hysell; Wyn Williams (Proceedings of the National Academy of Sciences, 2025)
The Red Planet is a magnetic planet. The Martian crust contains strong magnetization from a core dynamo that likely was active during the Noachian period when the surface may have been habitable. The evolution of the dynamo may have played a central role in the evolution of the early atmosphere and the planet’s transition to the current cold and dry state. However, the nature and history of the dynamo and crustal magnetization are poorly understood given the lack of well-preserved, oriented, ancient samples with geologic context available for laboratory study. Here, we describe how magnetic measurements of returned samples could transform our understanding of six key unknowns about Mars’ planetary evolution and habitability. Such measurements could i) determine the history of the Martian dynamo field’s intensity; ii) determine the history of the Martian dynamo field’s direction; iii) test the hypothesis that Mars experienced plate tectonics or true polar wander; iv) constrain the thermal and aqueous alteration history of the samples; v) identify sources of Martian crustal magnetization and vi) characterize sedimentary and magmatic processes on Mars. We discuss how these goals can be achieved using future laboratory analyses of samples acquired by the Perseverance rover.